To Optimize Human Resource Management Processes In Aviation Companies By Utilizing The Carrotspot Motivation Value Index (CMVI) - Marzenna MIŁEK; Małgorzata ŻMIGRODZKA (Communications of International Proceedings, 2024)
Article to: Project number: POIR.01.01.01-00-0854/19. Title: "Human-centric BI and AI solution for human resources management" Project co-financed by the European Regional Development Fund under the Smart Growth Operational Program for 2014-2020. Beneficiary: LUX MED Benefity Sp. z o.o. In the context of the growing influence of artificial intelligence, the role of HRM professionals is undergoing a period of significant transformation. A growing research is shedding light on the ways in which new technologies are reshaping the field, but still is avoid in literature that makes this study important. In the airline industry, the optimization of HRM processes is a crucial factor in achieving operational excellence and organizational success what give a motive behind the study. The methodology presented in the study is concerned with a comparative analysis of individual data obtained from platform using by airlines companys utilizing instruments such as the Carrotspot Motivation Value Index (CMVI). The synthesis of the research problem also takes into account an analysis of the literature review. The research conducted yielded tangible results that show the benefits of implementing tools such as CMVI, which can significantly improve HRM processes in aviation.
Keywords: BI; HRM; data matching; HRTech; software; airline